Strategi Branding Universitas Cokroaminoto Yogyakarta Melalui Konten Kreatif di Platform Sosial Media - Nashrul Mu'minin; Taufik Nugroho; Lely Nur Hidayah Syafitri; Muhammad Nur Kholis Al-Amin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This study analyzes the branding strategy of the UCY Islamic Religious Education Study Program through creative content on social media. With a descriptive qualitative approach through observation, interviews, and documentation, the results show that the use of attractive visuals, inspiring narratives, and consistent posting on Instagram and TikTok has succeeded in increasing interaction, emotional closeness, and institutional identity. The conclusion of the study proves the effectiveness of creative content in expanding the reach, audience engagement, and digital existence of UCY.